Shortage of paediatric radiologists acting as an expert witness: position statement from the British Society of Paediatric Radiology (BSPR) National Working Group on Imaging in Suspected Physical Abuse (SPA). Issue 7 (July 2019) - Oates, A.; Halliday, K.; Offiah, A.C.; Landes, C.; Stoodley, N.; Jeanes, A.; Johnson, K.; Chapman, S.; Stivaros, S.M.; Fairhurst, J.; Watt, A.; Paddock, M.; et al.
Abstract : One of the most challenging areas of radiological imaging in children is the diagnosis of physical abuse. There is a dearth of paediatric radiologists willing to act as expert witnesses, particularly in the family courts. There are a number of reasons why radiologists may not be interested or willing to put themselves forward to work as expert witnesses in this field. A group of imaging experts recently formed the "British Society of Paediatric Radiology (BSPR) Working Group on Imaging in Suspected Physical Abuse (SPA)". The group comprises radiologists and neuroradiologists with current or previous experience of providing expert witness reports to the court in cases of SPA. The group met in January 2019 to explore pragmatic solutions to the chronic inefficiencies in both medical and legal practices and the challenges that arise from working in a legal arena with different structures, goals, and assessment criteria. Key issues concerned organisational inefficiencies, variable support from National Health Service Trusts and the Royal College of Radiologists to conduct this work, and the risk/benefit of involvement. This work is important for the patient, parents, and society in general, and highly rewarding for clinical practitioners who are involved, but there are several issues with current practices that discourage active participation. With several members of the group either retired or close to retirement, the shortage of experts is becoming a pressing issue within the UK, which requires an engaged multidisciplinary group to come up with creative solutions. Here, the group provide a consensus opinion highlighting the current barriers and potential facilitators to increasing the number of radiologists willing to provide opinions to the court.